Program Kemitraan Masyarakat Peternak Sapi Desa Batuputih Bitung Provinsi Sulawesi Utara - Nangoy, Meis Jacinta; Onibala, Jane; Podung, Albert; Koneri, Roni; Sondakh, E.H.B (Universitas Sam Ratulangi, 2021)
The traditional cattle rearing system is the permanent host for various zoonotic diseases that are transmitted through insects. Flies and ticks are insects that harm farmers because they decrease productivity and spread disease from livestock to livestock and to humans. The community partnership program for cattle breeders in Batuputih Bitung village is a community education activity that aims to increase the understanding of nuisance insects and their potential problems, identify the types of nuisance insects and their potential control. This activity was conducted from April to September 2021 and involved a group of cattle breeders and the Sam Ratulangi University Faculty of Animal Husbandry team (lecturers and students). The method of implementing this activity was carried out in 3 stages, namely discussions and interviews, surveys of nuisance insects on cattle, and the practice of introducing insects and their control. The cattle farmers in Batuputih Village have understood the livestock pest insects and their potential problems. The types of nuisance insects identified were: Haematobia exigua, Stomoxys sp., Musca sp., Tabanus sp. and ticks and some of the traditional methods of controlling them. It is necessary to monitor the effectiveness of insect population control so that the potential for zoonoses that spread through insects can be prevented early.Keywords: insect; vector; disease; cattle; SurraÂ AbstrakSistem pemeliharaan ternak sapi yang bersifat tradisional dapat merupakan induk semang tetap berbagai penyakit zoonosis yang ditularkan melalui serangga. Lalat dan caplak merupakan serangga yang merugikan peternak karena menurun produktivitas dan menyebar penyakit dari ternak ke ternak dan ke manusia. Program kemitraan masyarakat peternak sapi desa Batuputih Bitung merupakan kegiatan edukasi masyarakat yang bertujuan meningkatkan pemahaman akan serangga pengganggu dan potensi permasalahannya. Kegiatan ini melibatkan kelompok peternak sapi dan tim Fakultas Peternakan Universitas Sam Ratulangi (dosen dan mahasiswa) dan dilaksanakan pada bulan April hingga September 2021. Metode pelaksanaan kegiatan dilakukan dalam 3 tahap yaitu diskusi dan wawancara, survey serangga pengganggu pada ternak sapi, dan praktek pengenalan serangga dan pengendaliannya. Peternak sapi Desa Batuputih telah memahami serangga pengganggu ternak (Haematobia exigua, Stomoxys sp., Musca sp., Tabanus sp. dan caplak) dan beberapa cara pengendaliannya secara tradisional. Diperlukan kegiatan pemantauan efektivitas pengendalian populasi serangga agar potensi zoonosis yang menyebaran melalui serangga dapat dicegah secara dini.Â Kata kunci: serangga; vektor; penyakit; sapi; Surra